Ódry Árpád színészetéről - Porogi, Dorka (Symbolon, 2021)
Árpád Ódry’s Art of Performance In 1896 the second-year academy student Árpád Ódry was already mentioned by critics as possessing the rare talent of being “able to speak”. The young journalist who first recognizes Ódry’s talent, Sándor Hevesi, will later become the director of the National Theatre. My research focuses on how Ódry’s methods represented an acting ideal and a new school at the beginning of the 20th century by introducing natural (but not naturalistic) performance methods. These methods have proved to have a lasting effect until the present. Ódry’s natural performance methods, however, can only be achieved with the special techniques of the acting profession.